Influence of the three‐dimensional culture of human bone marrow mesenchymal stromal cells within a macroporous polysaccharides scaffold on Pannexin 1 and Pannexin 3. (8th January 2018) - Guerrero, Julien; Oliveira, Hugo; Aid, Rachida; Bareille, Reine; Siadous, Robin; Letourneur, Didier; Mao, Yong; Kohn, Joachim; Amédée, Joëlle
Abstract: Because cell interactions play a fundamental role for cell differentiation, we investigated the expression of Pannexin 1 and Pannexin 3 in human bone marrow mesenchymal stromal cells (HBMSCs) in a three‐dimensional (3D) microenvironment provided by a polysaccharide‐based macroporous scaffold. The pannexin (Panx) family consists of three members, Panx1, Panx2, and Panx3. The roles of Panx large‐pore ion and metabolite channels are recognized in many physiological and pathophysiological scenarios, but the role of these proteins in human physiological processes is still under investigation. Our study demonstrates that HBMSCs cultured within 3D scaffolds have induced Panx1 and Panx3 expression, compared with two‐dimensional culture and that the Panx3 gene expression profile correlates with those of bone markers on mesenchymal stromal cells culture into the 3D scaffold. We showed that Panx1 is involved in the HBMSCs 3D cell–cell organization, as acting on the size of cellular aggregates, demonstrated by the use of Probenecid and the mimetic peptide 10panx1 as specific inhibitors. Inhibition of Panx3 using siRNA strategy shows to reduce the expression of osteocalcin as osteoblast‐specific marker by HBMSCs cultured in 3D conditions, suggesting a role of this Panx in osteogenesis. Moreover, we evaluated Panx1 and Panx3 expression within the cellularized scaffolds upon subcutaneous implantation in NOG (NOD/Shi‐ scid /IL‐2Rγ null ) mice, where we could observe a more intense expression in the constructs than in the surrounding tissues in vivo. This study provides new insights on the expression of pannexins in HBMSCs on a 3D microenvironment during the osteogenic differentiation, in vitro and in vivo.